1984
DOI: 10.1073/pnas.81.13.4090
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the structures of taxol and baccatine III derivatives and their in vitro action on the disassembly of mammalian brain and Physarum amoebal microtubules.

Abstract: The in vitro disassembly of microtubules from mammalian brain and Physarum is inhibited by various derivatives of taxol and baccatine III. Structure-activity relationships of the taxol derivatives were identical for both mammalian brain and Physarum microtubules. This observation suggests that the site of action of taxol has been preserved during the evolution of these two different eukaryotic lines. The substituent at C-13 of taxol was required to prevent disassembly of brain microtubules with or without micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
84
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 47 publications
5
84
0
Order By: Relevance
“…Structure-activity relationship studies have demonstrated that the C-2 benzoxy group, an intact oxetane ring bridged by the C-4(5) bond, and the C-13 O-[N-benzoyl (Bz) phenylisoserine] side chain of Taxol ( Fig. 1 A) are required for the unique tubulin-binding mode of action (6,7).…”
mentioning
confidence: 99%
“…Structure-activity relationship studies have demonstrated that the C-2 benzoxy group, an intact oxetane ring bridged by the C-4(5) bond, and the C-13 O-[N-benzoyl (Bz) phenylisoserine] side chain of Taxol ( Fig. 1 A) are required for the unique tubulin-binding mode of action (6,7).…”
mentioning
confidence: 99%
“…1), and these side chains are thought to be essential for stabilization of the microtubules. 12,13) All 18 taxane compounds used in this study lack such hydrophobic substitutions (Supplemental Fig. S3).…”
Section: Discussionmentioning
confidence: 99%
“…10,11) The N-benzoylphenylisoserine side chain at C-13 and the C-2 benzoyl group are essential for the stabilization of microtubules. 12,13) Chatterjee et al compared the dynamic properties of paclitaxel and those of one of its ''inactive'' analogs, baccatin III (Fig. 1C, 2), and concluded that they behave similarly in their interactions with tubulin.…”
mentioning
confidence: 99%
“…The resource of yew tree is limited, and the content of paclitaxel is so low in plant materials that it cannot meet the growing demand for paclitaxel for clinical trials [20,21]. However, other taxoids such as 10-DAB III and 7-xyl-10-DAT are presented in much higher quantities than paclitaxel in Taxus species, and pharmacological experiments indicated that 7-xyl-10-DAT exerted strong antitumour activity [22]. These taxoids can be transferred to paclitaxel or its derivatives through the biosynthesis or chemosynthesis methods [10, 12, 23 -26].…”
Section: Introductionmentioning
confidence: 99%